Results of an investigation into a group of patients presenting the symptoms of schizophrenia - Freed, Louis Franklin (Department of Psychology, 2020)
An investigation of the problem of schizophrenia necessitates in the first instance recourse to the following procedures: (I) A definition of the problem and a description of the symptomatology upon which the diagnosis of the disorder is based; (II) An elucidation of the methodological approach to the problem; and (III) A statment in regard to the sources of the clinical material which the investigator has utilised for the purpose of his research. These procedures are treated of in some detail in the ensuing sections.